Simultaneous reform on tariffs and quotas - James Peter Neary (University College Dublin, Department of Economics, 2005)
This paper presents a general result for simultaneous reform of taris and quotas in a small open economy, where some of the quota rents do not accrue to domestic residents. Absent highly perverse income eects, welfare must rise following a uniform proportionate reduction in taris and a uniform proportionate relaxation of quotas, weighted by their rent-retention parameters. Previous results are shown to be special cases of this one, and its implications for practical policy advice and its relationship with the policy of 'tarification' of quotas are noted.
hdl:10197/1791
Keywords: F13; 330; International trade policy; piecemeal policy reform; taris and quotas; tarification of quotas; trade liberalisation; voluntary export restraints trade liberalisation; voluntary export restraints.; Zollpolitik; Außenhandelskontingent; Reform; Theorie